The Plane of Mesh Placement Does Not Impact Abdominal Donor Site Complications in Microsurgical Breast Reconstruction. Issue 5 (November 2021) - Henn, Dominic; Sivaraj, Dharshan; Barrera, Janos A.; Lin, John Q.; Chattopadhyay, Arhana; Maan, Zeshaan N.; Chen, Kellen; Nguyen, Alan; Cheesborough, Jennifer; Gurtner, Geoffrey C.; Lee, Gordon K.; Nazerali, Rahim
Abstract : Background: Reinforcement of the abdominal wall with synthetic mesh in autologous breast reconstruction using abdominal free tissue transfer decreases the risk of bulging and herniation. However, the impact of the plane of mesh placement on donor site complications has not yet been investigated. Methods: We performed a retrospective analysis of 312 patients who had undergone autologous breast reconstruction with muscle-sparing transverse rectus abdominis myocutaneous (MS-TRAM) flaps or deep inferior epigastric perforator (DIEP) flaps as well as polypropylene mesh implantation at the donor site. Donor site complications were compared among patients with different flap types and different mesh positions including overlay (n = 90), inlay and overlay (I-O; n = 134), and sublay (n = 88). Results: Abdominal hernias occurred in 2.86% of patients who had undergone MS-TRAM reconstructions and in 2.63% of patients who had undergone DIEP reconstructions. When comparing patients with different mesh positions, donor site complications occurred in 14.4% of patients with overlay mesh, 13.4% of patients with I-O mesh, and 10.2% of patients with sublay mesh ( P = 0.68). Abdominal hernias occurred in 4.44% of patients with overlay mesh, 2.24% of patients with I-O mesh, and 2.27% of patients with sublay mesh ( P = 0.69). Multivariable logistic regression analysis did not identify a significant association between mesh position and hernia rates as well as wound complications. Conclusions: Our data indicate that the plane of synthetic mesh placement in relation to the rectus abdominis muscle does not impact the rate of postoperative donor site complications in patients undergoing breast reconstruction with MS-TRAM or DIEP flaps.